Prognostic Value of Right Ventricular Strains Using Novel Three-Dimensional Analytical Software in Patients With Cardiac Disease - Kitano, Tetsuji; Kovács, Attila; Nabeshima, Yosuke; Tokodi, Márton; Fábián, Alexandra; Lakatos, Bálint Károly; Takeuchi, Masaaki (Frontiers in Cardiovascular Medicine, 2022)
Background: Right ventricular (RV) three-dimensional (3D) strains can be measured using novel 3D RV analytical software (ReVISION). Our objective was to investigate the prognostic value of RV 3D strains. Methods: We retrospectively selected patients who underwent both 3D echocardiography (3DE) and cardiac magnetic resonance from January 2014 to October 2020. 3DE datasets were analyzed with 3D speckle tracking software and the ReVISION software. The primary end point was a composite of cardiac events, including cardiac death, heart failure hospitalization, myocardial infarction, or ventricular tachyarrhythmia. Results: 341 patients were included in this analysis. During a median of 20 months of follow-up, 49 patients reached a primary end point. In univariate analysis, RV ejection fraction (RVEF) and three strain values [RV global circumferential strain (RVGCS), RV global longitudinal strain (RVGLS), and RV global area strain (RVGAS)] were significantly associated with cardiac events (Hazard ratio: 0.846 to 0.932, p<0.05). Multivariate analysis revealed that RVEF, RVGCS, and RVGAS were significantly associated with future cardiac events after adjusting for age, chronic kidney disease, and left ventricular systolic/diastolic parameters. Kaplan-Meier survival curves showed that median values of RVEF, RVGCS, RVGLS, and RVGAS stratified a higher risk for survival rates. Classification and regression tree analysis, including 20 clinical and echocardiographic parameters, selected RVEF (cut-off value: 34.6%) first, followed by diastolic blood pressure (cut-off value: 53 mmHg) and RVGAS (cut-off value: 32.4%) for stratifying two high-risk group, one intermediate-risk group, and one low-risk group. Conclusions: Although RVEF was the best predictor, RV 3D strains, especially RVGAS provided an additional value for prognostication in a diverse group of patients with cardiac diseases.